Question 1: **Simplify the expression: **\((2-3i)(4+2i)\)

For this, we'll use the FOIL method.

2*4=8

8+__+__+__

2*2i=4i

8+4i+__+__

-3i*4=-12i

8+4i-12i+__

-3i*2i=-6i^{2}

(I'm assuming i=sqrt(-1))

8+4i-12i+6=14-8i

*Option S is your answer*

Question 2: **Simplify the expression:** \((3x^4+9x^3-7x+15)+(-6x^4-8x^2+5x-3)\)

This is adding like terms.

First, let's start with x^4

3-6=-3

-3x^{4}+9x^{3}-8x^{2}+__+__

There were only one x^3 and x^2 in the expression, so we know that part for sure.

Now, to the x term.

-7+5=-2

-3x^{4}+9x^{3}-8x^{2}-2x+__

Now, to the normal numbers.

15-3=12

*Final answer: -3x*^{4}+9x^{3}-8x^{2}-2x+12

Hope this helped!